STUDYING THE MOVEMENT (PRESESSION) OF THE GYROSCOPIC AXIS AND SOLVING RELATED PROBLEMS - Mansur Dusmuratov (Western European Studies, 2024)
This article provides examples of solving problems related to the causes of precessional gyroscope motion, the causes of precessional angular velocity and the moment of precession force and related methods, as well as tasks that students can solve on their own.
Keywords: precession; precessional motion; precession period; angular velocity of precession